PHYTOCHEMICAL SCREENING AND ANTIMICROBIAL ACTIVITIES OF PLANT EXTRACT OF TRIDAX PROCUMBENS - K. TEJASWINI; B. VISHWANATH PRADEEP; K. RUDRAMA DEVI; S. SHYLAJA; K. JYOTHSNA (The Bioscan, 2011)
Tridax procumbens Linn. (Compositae) is a weed found throughout India. The plant is native of tropical America and naturalized in tropical Africa, Asia, and Australia. Local people known it as “Ghamara”, in English popularly called ‘coat buttons’ and is dispensed for “Bhringraj” by some of the practitioners of Ayurveda. The phytochemical screening revealed the presence of alkaloids, carotenoids, flavonoids (catechins and flavones), fumaric acid, fl-sitosterol, saponins and tannins. Natural products continue to play an important role in the discovery and development of new pharmaceuticals, as clinically useful drugs, as starting materials to produce synthetic drugs, or as lead compounds from which a totally synthetic drug can be designed. The present study is designed for phytochemical analysis of Tridax procumbens and HPLC analysis. This also includes the antimicrobial activity of the bio active compound obtained by crude extract and the column chromatography.